Hyper-separation as a tool for work/life balance: Commuting in academia. (1st October 2020) - Sallee, Margaret W.; Lewis, Danielle V.
ABSTRACT: Given the declining number of tenure-track positions, the academic job market has become fiercely competitive, often forcing faculty to make difficult choices, including living apart from their partners and children. These individuals become commuting couples, neatly segmenting their professional and personal lives, and thus creating a hyper-separation between work and family. Using work/family border theory as an analytical lens, we draw on interviews with 36 participants who were members of commuting couples to explore how participants fared in this arrangement. Participants discussed how being separated both facilitated their professional productivity and deepened their personal relationships. In short, participants were engaged in an extreme form of work/life balance. We term this phenomenon the hyper-separation of roles, which serves as a mechanism to enact balance.